2019
DOI: 10.1590/1678-992x-2017-0394
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping for angular leaf spot severity and its implication in breeding common bean for resistance

Abstract: Phenotyping for severity of angular leaf spot (ALS) in common bean is important to identify new sources of resistance and select progenies in conventional and molecular markerassisted breeding. In this study, three phenotyping methods for ALS severity were assessed and its implications in breeding for resistance to Pseudocercospora griseola are discussed. Reaction of 144 common bean lines to P. griseola was evaluated. Three different experiments were conducted in the greenhouse (V2 and V3 stages) and in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The results of linkage mapping using AND 277 as an Andean source of resistance for the AM population showed the complexity of the resistance mechanism during an incompatible interaction between bean and P. griseola. Furthermore, ALS resistance is modulated by different QTL throughout the plant growth stage, corroborating the results shown phenotypically by Pereira R. et al (2019). The same result was observed for GWAS analysis, with significance of several QTNs for the three PGSs evaluated in the CDP of Mesoamerican origin, some QTNs being significant for more than one stage.…”
Section: Genome-wide Associationsupporting
confidence: 83%
See 3 more Smart Citations
“…The results of linkage mapping using AND 277 as an Andean source of resistance for the AM population showed the complexity of the resistance mechanism during an incompatible interaction between bean and P. griseola. Furthermore, ALS resistance is modulated by different QTL throughout the plant growth stage, corroborating the results shown phenotypically by Pereira R. et al (2019). The same result was observed for GWAS analysis, with significance of several QTNs for the three PGSs evaluated in the CDP of Mesoamerican origin, some QTNs being significant for more than one stage.…”
Section: Genome-wide Associationsupporting
confidence: 83%
“…In addition, Pereira et al (2015) showed the existence of great variability in virulence for isolates classified as the same race and studies have shown that genetic control of ALS resistance differs depending on the plant tissue affected (Borel et al, 2011;Rezende et al, 2014). Other studies also reported the genotype × environment interaction for evaluations under conditions of natural occurrence of the pathogen, showing a large environmental effect on control of resistance, corroborating the quantitative profile of the disease (Amaro et al, 2007;Oblessuc et al, 2012;Pereira R. et al, 2019). Pereira R. et al (2019) evaluated 144 bean accessions for ALS resistance in three different PGSs, and showed that the percentage of genotypes considered resistant to ALS ranging from 7% to 31%, and that the variation in the percentage of coincidence as low for qualitative inheritance.…”
Section: Qtl Associated With Als Resistancementioning
confidence: 59%
See 2 more Smart Citations
“…Fritsche-Neto et al (2019) reported an estimated heritability of 0.64 for anthracnose under field conditions and SNPs associated to ANT on Pv02 and heritability of 0.93 and SNPs associated for ALS on Pv10. Pereira et al (2019) demonstrated an observed heritability of 0.79 under conditions of natural incidence of angular leaf spot.…”
Section: Discussionmentioning
confidence: 99%